Cryptococcal meningoencephalitis relapse after an eight-year delay: an interplay of infection and immune reconstitution. (October 2015) - Katchanov, Juri; Blechschmidt, Cristiane; Nielsen, Kirsten; Branding, Gordian; Arastéh, Keikawus; Tintelnot, Kathrin; Meintjes, Graeme; Boulware, David R; Stocker, Hartmut
We report a case of a symptomatic relapse of HIV-related cryptococcal meningoencephalitis eight years after the first diagnosis on the background of immune reconstitution. The findings as well as the clinical course suggests a combination of smouldering localised infection and enhanced inflammatory reaction related to immune restoration due to antiretroviral therapy. A combination of antifungal and anti-inflammatory therapy resulted in clinical and radiological improvement. Our case challenges the concept that immune reconstitution inflammatory syndrome and microbiological relapse are dichotomous entities.